Effectiveness of Standard Operating Procedures on Elective Surgery Waiting Time at Bhayangkara TK II Medan Hospital - Sri Lestari Ramadhani Nasution; Zulhilmi Zulhilmi; Ermi Girsang (Universitas Islam Negeri Sumatera Utara, Medan, 2026)
Background: Inefficient implementation of Standard Operating Procedures (SOPs) can prolong waiting times for elective surgeries, which can lead to decreased service quality, increased risk of postoperative complications, and decreased patient satisfaction in hospitals. Objective: To evaluate the impact of Standard Operating Procedure implementation on reducing waiting times for elective surgeries in hospitals. Methods: This study used a qualitative approach with a descriptive case study design and data collection techniques through observation and in-depth interviews with one specialist doctor, one nurse, and one administrative staff member. The results were analyzed using the thematic method from Braun and Clarke (2021). Results: The study showed that the implementation of Standard Operating Procedures (SOPs) had a positive impact on managing waiting times for elective surgeries at Bhayangkara Hospital Level II Medan. SOPs helped accelarate the service process through a more structured workflow, clear division of tasks, and increased coordination and administrative efficiency. Based on the results of the study, the average waiting time for elective surgeries at Bhayangkara Hospital Level II Medan after the implementation of SOPs was less than one week from the time the patient was scheduled for surgery, demonstrating the effectiveness of SOP implementation in accelerating service. Conclusion: SOP plays an important role in reducing waiting times for elective surgery by increasing the effectiveness of medical and administrative services and strengthening communication between service units. Keywords: Standard Operating Procedures, Waiting Time, Elective Surgery, Service Efficiency, Hospital.